Play to win : - La Piana, David (Jossey-Bass, 2005)
Play to Win offers nonprofit leaders the help they need to develop their organization’s unique competitive advantages and to use the power of competitive strategies to build their organization’s capacity for advancing its mission. This book offers a clear description of competition and discusses its practical, ethical, and political ramifications within the nonprofit sector. It demonstrates how, by being a more effective competitor, a nonprofit can enhance its chances for both programmatic and financial success. Play to Win is filled with practical tools for assessing a nonprofit’s position in the marketplace and developing winning competitive strategies